2011
DOI: 10.1248/jhs.57.184
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Dimethylmatairesinol as an Immunoglobulin E-suppressing Component of the Leaves of Cinnamomum camphora

Abstract: Immunoglobulin E (IgE) plays an important role in allergic diseases. In this study, we found that a methanol extract of leaves of the camphor tree Cinnamomum camphora (C. camphora) reduced the amount of IgE secreted by human myeloma U266 cells. When the methanol extract was fractionated by extraction with organic solvents, the ethyl acetate fraction showed the highest activity. The fraction was further separated into several subfractions by preparative TLC. We identified the component of one of the active subf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…Cinnamomum camphora (L.) Presl (family: Lauraceae) is a Chinese medicinal plant widespread in China and has long been prescribed in traditional medicine for treatment of inflammation-related diseases, such as rheumatism, sprains, bronchitis, and muscle pains [7]. Pharmacological studies have revealed that the plant possesses a wide range of therapeutic activities, including anthelmintic [8], sperm viability effect [9], antibacterial [10], antiallergic [11], and antiinflammatory [12]. C. camphora is a well-known chemotype; on distillation, the wood from different groups of trees may yield camphor, linalool, safrole, or cineole as the major chemical.…”
Section: Introductionmentioning
confidence: 99%
“…Cinnamomum camphora (L.) Presl (family: Lauraceae) is a Chinese medicinal plant widespread in China and has long been prescribed in traditional medicine for treatment of inflammation-related diseases, such as rheumatism, sprains, bronchitis, and muscle pains [7]. Pharmacological studies have revealed that the plant possesses a wide range of therapeutic activities, including anthelmintic [8], sperm viability effect [9], antibacterial [10], antiallergic [11], and antiinflammatory [12]. C. camphora is a well-known chemotype; on distillation, the wood from different groups of trees may yield camphor, linalool, safrole, or cineole as the major chemical.…”
Section: Introductionmentioning
confidence: 99%
“…Kafoor (C. camphora) has been reported to exhibit several biological activities such as antiviral 43 , antimicrobial 43,44 , insecticidal 45 , antitussive 46,47 , antiinflammatory and antioxidant 48 , anti-allergic 49 , antimutagenic and anticancer 43 activities.…”
Section: 37mentioning
confidence: 99%
“…The combined effects of phytocompounds present in the formulation may yield a synergistic effect with potentially enhanced biological activities. Moreover, the formulation may also prove beneficial in providing symptomatic relief in patients affected with COVID-19, as the formulation ingredients and their phytocompounds have been reported to exhibit antiallergic, antitussive and bronchodilatory activities 46,47,49,[61][62][63] . Hence, it is rational to state that the formulation may prove effective in augmenting the immune status, alleviating inflammatory responses and suppressing the virulence of SARS-CoV-2.…”
Section: Plausible Role Of Arq Ajib In Combating Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Lignans are attracting considerable attention due to their widespread distribution in plants and their varied bioactivity. 1–5 For example, matairesinol, 2 dimethylmatairesinol, 3 yatein, 4 and niranthin 5 are found in nature and exhibit e.g. , cytotoxicity, 2 b , d ,3 b ,4 b anti-bacterial, 2 c anti-allergic, 3 c anti-viral, 4 d ,5 b , e anti-leishmanial, 5 d and strong insect-feeding-deterrent activity.…”
mentioning
confidence: 99%